(untitled) (Papeles, 2023)
This presentation arises from the research project: "Historical Reconstruction of the Center for Social Assistants of Santa Fe 1st Circumscription (1946-1986)", which is part of the current Professional Association of Social Assistants. From the archival work carried out, we find different activities tending to the conformation and legitimization of the incipient professional field, carried out by the first graduates of the Center. We will stop at the First Provincial Conference of Social Service in Santa Fe in 1947, as a professional event that outlines a first political experience of organization, debates and inquiry practices on the social problems of that time. Based on the papers presented at the Conference, we contextualize the lines of discussion on social issues and identify the theoretical arguments, methodological proposals, and philosophical ideas and foundations that give rise to the profession in the local context. Then, we reflect on its reconfigurations and persistence in current academic debates.